2011
DOI: 10.1161/atvbaha.111.225490
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Stimulates Low-Density Lipoprotein Receptor–Related Protein-1 Expression Through Hypoxia-Inducible Factor-1α in Human Vascular Smooth Muscle Cells

Abstract: Objective-Hypoxia is considered a key factor in the progression of atherosclerotic lesions. Low-density lipoprotein receptor-related protein (LRP1) plays a pivotal role in the vasculature. The aim of this study was to investigate the effect of hypoxia on LRP1 expression and function in vascular smooth muscle cells (VSMC) and the role of hypoxia-inducible factor-␣ (HIF-1␣). Methods and Results-Real-time polymerase chain reaction and Western blot analysis demonstrated that hypoxia (1% O 2 ) time-dependently indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
55
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 56 publications
3
55
0
Order By: Relevance
“…Hypoxia, however, strongly increased pPyk2 staining in hVSMCs ( Figure 1E). As previously shown in hVSMCs, 16 HIF-1α levels were significantly increased at 4 and 8 hours of mVSMCs ( Figure IE …”
supporting
confidence: 83%
See 2 more Smart Citations
“…Hypoxia, however, strongly increased pPyk2 staining in hVSMCs ( Figure 1E). As previously shown in hVSMCs, 16 HIF-1α levels were significantly increased at 4 and 8 hours of mVSMCs ( Figure IE …”
supporting
confidence: 83%
“…Previous studies from our group showed that hypoxia strongly upregulated LRP1 expression in hVSMCs. 16 Here, we show that LRP1 expression and Pyk2 phosphorylation were concomitantly upregulated by hypoxia for ≤32 hours in hVSMCs. According to our results, hypoxia modulates LRP1 and pPyk2 levels in a specific manner depending on species and cell type.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…HIF-1a is a known factor that can induce LRP1 expression in cardiomyocytes 42 and in other cell types. [43][44][45][46] These effects were lost following chronic diabetes, and could contribute to the development of cardiomyopathy in these animals. The disappearance of LRP1, with prolonged duration of diabetes, may be related to a further attenuation of myocytes pooled from four independent experiments.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Uptake of agLDL through LRP1 allows high-intracellular CE accumulation not only because of its high capacity to bind and internalize agLDL, but also because LRP1 is transcriptionally upregulated by intracellular cholesterol. Our group reported that LRP1 is upregulated at transcriptional level by hypercholesterolemia through sterol regulatory element-binding proteins (SREBP) downregulation in human VSMC, [8][9][10] and by hypoxia through hypoxia-inducible factor 1α upregulation in human VSMC 11 and cardiomyocytes. 12,13 Other groups have reported that insulin promotes the presence of LRP1 in the plasma membrane without influencing mRNA expression levels.…”
mentioning
confidence: 99%